Hormonal therapy in the senescence: Prostatic microenvironment structure and adhesion molecules - Montico, Fabio; Hetzl, Amanda Cia; Candido, Eduardo Marcelo; Favaro, Wagner Jose [UNESP]; Alves Cagnon, Valeria Helena (Pergamon-Elsevier B.V. Ltd, 2011)
Hormonal replacement has been utilized to minimize the harmful effects of hormonal imbalance in elderly men. The development and progression of prostatic diseases and their relation to hormone therapy is still unclear. Thus, the aim herewith was to characterize the structure and dystroglycan molecule (DGs) reactivities in the ventral prostatic lobe from elderly rats submitted to steroid hormone replacement. Male rats (Sprague-Dawley) were divided into one Young group and six senile groups. The Young group (YNG) (4 months old) received peanut oil (5 mL/kg, s.c.). The senile rats (10 months old) were submitted to the following treatments: Senile group (SEN) (5 mL/kg peanut oil, s.c.); Testosterone group (TEST) (5 mg/kg testosterone cipionate, s.c.); Estrogen group (EST) (25 mu g/kg 17 beta-estradiol, s.c.); Castrated group (CAS) (surgical castration); Castrated-Testosterone (CT) (surgical castration and treatment similar to TEST group); and Castrated-Estrogen (CE) (surgical castration and treatment similar to EST group). After 30 days treatment, blood samples were collected for hormonal analysis and ventral prostate samples were processed for light and transmission electron microscopies, morphometrical analysis, immunohistochemistry and Western Blotting. The results showed decreased serum testosterone levels in the senescence and increased testosterone and estrogen plasmatic levels after hormone administration in the TEST and EST groups, respectively, highlighting the therapy efficiency. Hypertrophied stroma and inflammatory cells were verified in the SEN group. After hormone replacement in the senescence or following castration, atrophic epithelium, epithelial cells with clear cytoplasmic halo around the nucleus, microacini and maintenance of hypertrophied stroma were seen. Decreased DG levels were verified in the senescence. After hormonal therapy, increased protein levels of these molecules were observed, especially in those groups which received estradiol. Thus, the occurrence of inflammatory cells, stromal hypertrophy and the presence of cells with clear halo around the nucleus after hormonal therapy probably indicated prostatic paracrine signaling imbalance, suggesting a stromal reactive microenvironment favorable to the development of glandular lesions. However, the increase of DG levels characterized positive effect of steroid hormone replacement on the prostate in the senescence. Thus, it could be concluded that despite having positive effects on important molecules involved in the maintenance of epithelial-stromal interaction and glandular cytoarchitecture, such as DGs, hormonal therapy enhanced structural changes associated with senescence, probably due to increased hormonal imbalance between androgens and estrogens in the prostatic tissue. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Prostate; Senescence; Steroid hormones; Ultrastructure; Dystroglycans